High-throughput single-fly LC–MS/MS for quantitative profiling of biogenic amines in Drosophila - Aki Hori; Takahiro Nitta; Kei-ichiro Inamori; Hirotaka Kanoh; Takayuki Kuraishi (PLoS ONE, 2026)
We present an LC–MS/MS method that enables reproducible, quantitative detection of multiple biogenic amines—including octopamine, dopamine, serotonin, and their precursors—from single Drosophila individuals. The workflow involves only a minimal extraction in methanol prior to direct injection, eliminating the need for derivatization or laborious purification steps. Its simplicity ensures high reproducibility and broad applicability across experimental settings. Pilot applications revealed distinct neurochemical responses across biologically relevant conditions: a circadian rise in octopamine at dusk, acute increases in octopamine, dopamine, and serotonin under cold stress, and elevations of octopamine, serotonin, and tryptophan during starvation. These findings highlight the utility of single-head LC–MS/MS for dissecting neuromodulator dynamics at the level of individual organisms.